2018
DOI: 10.1597/16-006
|View full text |Cite|
|
Sign up to set email alerts
|

Microarchitecture and Biomechanical Evaluation of BoneCeramic Grafted Alveolar Defects during Tooth Movement in Rat

Abstract: BoneCeramic has better osteoconductive potential and biomechanical properties and induces less root resorption compared with Bio-Oss grafting and naturally recovered extraction site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(36 citation statements)
references
References 19 publications
0
36
0
Order By: Relevance
“…These cleft defects are unique with regard to the associated soft-tissue connection of the oral and nasal mucosa. In this context, various experimental cleft models in rats have been used to investigate cleft repair techniques and grafting materials 12 20 . However, these models did not coincide with a clinical cleft, where the epithelium lining is defective.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These cleft defects are unique with regard to the associated soft-tissue connection of the oral and nasal mucosa. In this context, various experimental cleft models in rats have been used to investigate cleft repair techniques and grafting materials 12 20 . However, these models did not coincide with a clinical cleft, where the epithelium lining is defective.…”
Section: Discussionmentioning
confidence: 99%
“…Different rat models have been presented for cleft research 12 20 , but most models are not in accord with the clinical situation in which the defect is covered by the epithelial lining. In these cleft models the bone defect is created and filled in the same operation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, TCP graft has shown several potentials to be used as a substitution of autograft materials instead. 5 TCP grafts have also been widely used by orthopedic surgeons to repair bone defects in certain clinical conditions. Leucht P et al showed that there were no significant differences of functional scores between the use of TCP graft and autograft in repairing acetabulum fractures with marginal impaction.…”
Section: Discussionmentioning
confidence: 99%